Intima-media thickness evolution after treatment with infliximab in patients with rheumatoid arthritis - Pierpaolo Di Micco; Paola Ferrazzi; Luca Librè; et al. (International Journal of General Medicine, 2009)
Pierpaolo Di Micco1,2, Paola Ferrazzi1, Luca Librè1, Loredana Mendolicchio1, Ilaria Quaglia1, Monica De Marco1, Anna Colombo1, Monica Bacci1, Lidia Luciana Rota1, Corrado Lodigiani11Thrombosis Center, Istituto Clinico Humanitas, Rozzano (MI), Italy; 2Internal Medicine, Fatebenefratelli Hospital of Naples, ItalyBackground: Atherosclerosis is a well known progressive disease that recognizes risk factors such as diabetes, hypertension, smoking, dyslipidemia, and inflammation. Mechanisms underlying atherosclerotic processes during inflammation are not completely understood, but cytokines are also involved, in particular tumor necrosis factor-α (TNF-α). Chronic inflammatory diseases such as rheumatoid arthritis (RA) are commonly associated with atherosclerotic complication. Little is known about the role of treatment of chronic inflammatory disease on the evolution of atherosclerosis in this kind of disease. Usually, evolution of atherosclerosis is monitored by intimamedia thickness and the presence of plaques on several arteries such as common carotid. Aim: The aim of the study was to monitor atherosclerosis evolution in seven RA patients on common treatment with infliximab (an anti-TNF-α drug) compared with seven RA patients during common treatment but not treated with infliximab. Patients and methods: We selected 14 patients with RA according to the American College of Rheumatology classification criteria. Seven patients were selected before and after common treatment for RA based on nonsteroidal anti-inflammatory drugs (NSAIDs), methotrexate, and steroids (12 months), and seven patients before and after treatment based on infliximab associated with NSAIDs, methotrexate, and steroids (12 months). Ultrasound vascular imaging was performed to screen intima-media thickness and the presence of atherosclerotic plaques on common carotid artery and identify evolution of atherosclerosis.Results: After 12 months, patients that were treated with infliximab showed significant worsening of atherosclerosis with an increase of intima-media thickness and the presence of further atherosclerotic plaques compared to patients that were treated traditionally and showed a nonsignificant increase of the same parameters. Discussion: Treatment based on anti-TNF-α such as infliximab shows a worsening evolution of atherosclerosis based on our data. If these data are associated with a poor clinical outcome such as atherothrombosis of cerebral vessels and/or coronary vessels, this should be evaluated by further studies.Keywords: atherosclerosis, infliximab, rheumatoid arthritis, intima-media thickness